PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN: KAJIAN LITERATUR MENGENAI METODE, PROSEDUR, DAN IMPLIKASINYA TERHADAP PENINGKATAN KOMPETENSI PENDIDIK - Mawarna Febriani; Barokah Isdaryanti; Joko Sutarto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Human resource development (HRD) in education plays a crucial role in improving educator quality and overall educational outcomes. The demands of globalization and rapid technological advancement require educators to continuously enhance their pedagogical, professional, social, and personal competencies. This article aims to examine the methods and procedures of human resource development in education and their implications for improving educator competencies. This study employs a literature review method by analyzing relevant scholarly articles, books, and previous research related to human resource development in educational settings. Data were analyzed through the processes of identification, selection, evaluation, and synthesis of findings from selected sources. The review reveals that human resource development in education can be implemented through various methods, including training programs, workshops, academic supervision, mentoring, coaching, continuous professional development, and the integration of technology in learning. The procedures generally involve needs assessment, program planning, implementation, evaluation, and follow-up actions. Furthermore, the findings indicate that systematic and sustainable human resource development positively contributes to the improvement of educators’ pedagogical, professional, social, and personal competencies. Therefore, human resource development serves as an essential strategy for enhancing educational quality and strengthening educator professionalism.